Fate of Heavy Metals Pb and Zn in the West Season at Jeneberang Estuary, Makassar - Najamuddin .; Tri Prartono; Harpasis S Sanusi; I. Wayan Nurjaya (Marine Science Department Diponegoro University, 2017)
The pollutant quantity of heavy metals entering water environment does not give complete answer toward the generated effect and risk, however it needs thoroughly study related to the pollutant dynamic. The aim of this research was to investigate the fate of Pb and Zn in water, such as: distribution, behavior, and reactivity (case study: Jeneberang Estuary, Makassar). Pb and Zn concentrations were determined using Atomic Absorption Spectrophotometry (AAS). The distribution of dissolved Pb and Zn showed a pattern that the lowest concentration was in the fresh water (the river zone), whereas the highest concentration was in the salt water (the marine zone). The distribution pattern of particulate Pb and Zn showed that the highest concentration was in the fresh water (the river zone) and the salt water (the marine zone), whereas the lowest concentration was in the estuary zone. The behavior of dissolved Pb and Zn tended to increase the concentration (desorption) along the increased salinity gradient. The residual fraction was the dominant component of geochemical fractions in the sediment that indicated the sources of Pb and Zn mainly derived from a natural process and the reactivity was low in the water. Keywords: distribution, behavior, reactivity, lead, zinc, pollution